THE INFLUENCE OF SOCIAL FACTORS ON CUSTOMER PURCHASE INTENTION IN USING WEDDING ORGANIZER IN MANADO - Tuwo, Hillary Julia; Pandowo, Merinda (FEB Universitas Sam Ratulangi Manado, 2015)
Trends in wedding business is being exported globally. There is market opportunity to make the proliferation of event organizer business to become wedding organizer. The Wedding organizer business is needed at this time for the success of wedding preparation and ceremony. Now social influences are not new to the wedding industry because most of the time couples, especially brides-to-be, are consulting to external parties in order to acquire ideas and suggestions on how to enrich the context and design of the wedding celebration. The purpose of this study is to analyze the influence of social factors on customers purchase intention in using wedding organizer in Manado. The research method used in this research is associated with multiple linear regression analysis, and the sample of 60 respondents were taken from couples-to-be and married couples. The result reveales that reference groups, family, and roles & status have a significant influence and family is the most dominant to the customers purchase intention in using wedding organizers. The role of parents are very important and influential. At certain ages, young people cannot generate their own income so family automatically becomes a source of funds in facilitating customers in purchase wedding organizers. Â Keywords: reference group, family, roles and status, purchase intention